Pharmacy students’ motivations, satisfaction, and future career plans: A cross-sectional study exploring gender differences - Nadine N. Abdelhadi; Ayat Al-Meanazel; Lidia Kamal Al-Halaseh; Mervat M. Alsous; Samah Al-Shatnawi; Anwar Abdel Qader Jaffal; Mohammad Yasin Mohammad; Rula M. Darwish (PLoS ONE, 2025)
Background The pharmacy profession has significantly changed over the years. Pharmacy students’ perceptions of their coursework and future career aspirations may vary in relation to gender. Objectives The present study explored the motivations of pharmacy students to enter pharmacy school, their satisfaction with the academic program, future plans after graduation, and perceptions about the pharmacy profession in relation to gender. Methods Data were collected using a cross-sectional descriptive validated questionnaire built by the research team. The study was conducted at twelve public and private universities offering pharmacy programs. Results In total, 918 pharmacy students have completed the online questionnaire, with a 98% response rate. Most participants reported that family encouragement was a motive to enter pharmacy school. The results of the Chi-Squared Test indicated a significant difference between female and male participants with respect to the following motives: High school grades (p = 0.009), being good at science (p = 0.013), working with patients(p = 0.024), professional status (p = 0.014), working in a family business (p = 0.001) and job opportunities (p = 0.001). The majority of male participants and female participants perceived pharmacy jobs as prestigious jobs. In addition, male and female students believed that it was a profession with well-paid jobs. Conclusion Females were significantly more motivated by their high school degrees, goodness at science, working with patients, and professional status to enter pharmacy school. Pharmacy students are satisfied enough with the academic program. Male and female pharmacists have different career aspirations in the pharmaceutical sectors. It is recommended that students be educated about career planning to help them accomplish their goals. Future research could benefit from longitudinal studies to explore changes in pharmacy students’ motivations, satisfaction, and career aspirations over time.